Selective recognition of ATP by multivalent nano-assemblies of bisimidazolium amphiphiles through “turn-on” fluorescence response - Biswas, Rakesh; Ghosh, Surya; Bhaumik, Shubhra Kanti; Banerjee, Supratim (Beilstein Journal of Organic Chemistry, 2020)
Bisimidazolium receptors, tagged with chromophoric pyrene at one end and linked to an n-alkyl chain at the other, underwent self-assembly in aqueous media depending on the length of the alkyl segment. The amphiphilic derivatives having n-decyl or longer chains, formed nano-assemblies with cyanic–green emission resulting from the stacked pyrene chromophores in the aggregates. The presence of positive surface charges on the multivalent aggregates led to ATP binding which was accompanied by a significant increase in the excimeric emission intensity. This provided a convenient way of monitoring ATP binding in a “turn-on” mode and an efficient detection of ATP was achieved in aqueous buffer and also in buffer containing 150 mM NaCl at physiological pH value. Furthermore, the multivalent aggregates demonstrated a significant selectivity in ATP detection over ADP, AMP and pyrophosphate.
Keywords: amphiphile; ATP; excimer; multivalency; self-assembly

(untitled) - Busschaert, N.; Caltagirone, C.; Van Rossom, W.; Gale, P. A. (Chem. Rev., 2015)

(untitled) - Flood, A. H. (Beilstein J. Org. Chem., 2016)

(untitled) - Wu, J.; Zou, Y.; Li, C.; Sicking, W.; Piantanida, I.; Yi, T.; Schmuck, C. (J. Am. Chem. Soc., 2012)

(untitled) - Maity, D.; Schmuck, C. (Chem. – Eur. J., 2016)

(untitled) - Maeda, H. (Chem. – Eur. J., 2008)

(untitled) - Zhang, Z.; Kim, D. S.; Lin, C.-Y.; Zhang, H.; Lammer, A. D.; Lynch, V. M.; Popov, I.; Miljanić, O. Š.; Anslyn, E. V.; Sessler, J. L. (J. Am. Chem. Soc., 2015)

(untitled) - You, L.; Zha, D.; Anslyn, E. V. (Chem. Rev., 2015)

(untitled) - Mammen, M.; Choi, S.-K.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Badjić, J. D.; Cantrill, S. J.; Stoddart, J. F. (J. Am. Chem. Soc., 2004)

(untitled) - Crespo-Biel, O.; Lim, C. W.; Ravoo, B. J.; Reinhoudt, D. N.; Huskens, J. (J. Am. Chem. Soc., 2006)

(untitled) - Badjić, J. D.; Nelson, A.; Cantrill, S. J.; Turnbull, W. B.; Stoddart, J. F. (Acc. Chem. Res., 2005)

(untitled) - Lee, Y. C.; Lee, R. T. (Acc. Chem. Res., 1995)

(untitled) - Lin, B.; Qing, X.; Liao, J.; Zhuo, K. (Cells, 2020)

(untitled) - Krachler, A. M.; Ham, H.; Orth, K. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Fasting, C.; Schalley, C. A.; Weber, M.; Seitz, O.; Hecht, S.; Koksch, B.; Dernedde, J.; Graf, C.; Knapp, E.-W.; Haag, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Liang, J.; Li, K.; Liu, B. (Chem. Sci., 2013)

(untitled) - Feng, X.; Liu, L.; Wang, S.; Zhu, D. (Chem. Soc. Rev., 2010)

(untitled) - Rochat, S.; Swager, T. M. (ACS Appl. Mater. Interfaces, 2013)

Multivalency: Concepts, Research and Applications - Huskens, J.; Prins, L. J.; Haag, R.; Ravoo, B. J. (John Wiley & Sons, 2018)

(untitled) - Dreher, M. R.; Simnick, A. J.; Fischer, K.; Smith, R. J.; Patel, A.; Schmidt, M.; Chilkoti, A. (J. Am. Chem. Soc., 2008)

(untitled) - Kingery-Wood, J. E.; Williams, K. W.; Sigal, G. B.; Whitesides, G. M. (J. Am. Chem. Soc., 1992)

(untitled) - Drożdż, W.; Walczak, A.; Bessin, Y.; Gervais, V.; Cao, X.-Y.; Lehn, J.-M.; Ulrich, S.; Stefankiewicz, A. R. (Chem. – Eur. J., 2018)

(untitled) - Rodrigo, A. C.; Barnard, A.; Cooper, J.; Smith, D. K. (Angew. Chem., Int. Ed., 2011)

(untitled) - Rajangam, K.; Behanna, H. A.; Hui, M. J.; Han, X.; Hulvat, J. F.; Lomasney, J. W.; Stupp, S. I. (Nano Lett., 2006)

(untitled) - Xu, Z.; Jia, S.; Wang, W.; Yuan, Z.; Ravoo, B. J.; Guo, D.-S. (Nat. Chem., 2019)

(untitled) - Sandanaraj, B. S.; Vutukuri, D. R.; Simard, J. M.; Klaikherd, A.; Hong, R.; Rotello, V. M.; Thayumanavan, S. (J. Am. Chem. Soc., 2005)

(untitled) - Bhaumik, S. K.; Patra, Y. S.; Banerjee, S. (Chem. Commun., 2020)

(untitled) - Knowles, J. R. (Annu. Rev. Biochem., 1980)

(untitled) - Higgins, C. F.; Hiles, I. D.; Salmond, G. P. C.; Gill, D. R.; Downie, J. A.; Evans, I. J.; Holland, I. B.; Gray, L.; Buckel, S. D.; Bell, A. W.; Hermodson, M. A. (Nature, 1986)

(untitled) - Yu, M.; Yao, Y.; Cui, B.; Sun, C.; Zhao, X.; Wang, Y.; Liu, G.; Cui, H.; Zeng, Z. (ACS Appl. Nano Mater., 2019)

(untitled) - Bhowmik, S.; Ghosh, B. N.; Marjomäki, V.; Rissanen, K. (J. Am. Chem. Soc., 2014)

(untitled) - Weitz, E. A.; Chang, J. Y.; Rosenfield, A. H.; Morrow, E. A.; Pierrre, V. C. (Chem. Sci., 2013)

(untitled) - Kurishita, Y.; Kohira, T.; Ojida, A.; Hamachi, I. (J. Am. Chem. Soc., 2012)

(untitled) - Ngo, H. T.; Liu, X.; Jolliffe, K. A. (Chem. Soc. Rev., 2012)

(untitled) - Hargrove, A. E.; Nieto, S.; Zhang, T.; Sessler, J. L.; Anslyn, E. V. (Chem. Rev., 2011)

(untitled) - Zuo, X.; Song, S.; Zhang, J.; Pan, D.; Wang, L.; Fan, C. (J. Am. Chem. Soc., 2007)

(untitled) - Tang, Z.; Mallikaratchy, P.; Yang, R.; Kim, Y.; Zhu, Z.; Wang, H.; Tan, W. (J. Am. Chem. Soc., 2008)

(untitled) - Liu, Z.; Chen, S.; Liu, B.; Wu, J.; Zhou, Y.; He, L.; Ding, J.; Liu, J. (Anal. Chem. (Washington, DC, U. S.), 2014)

(untitled) - Zhou, Q.; Swager, T. M. (J. Am. Chem. Soc., 1995)

(untitled) - Parthasarathy, A.; Pappas, H. C.; Hill, E. H.; Huang, Y.; Whitten, D. G.; Schanze, K. S. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Cui, Q.; Yang, Y.; Yao, C.; Liu, R.; Li, L. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Zhao, Q.; Zhang, Z.; Tang, Y. (Chem. Commun., 2017)

(untitled) - Huang, H.; Tan, Y.; Shi, J.; Liang, G.; Zhu, J.-J. (Nanoscale, 2010)

(untitled) - Zhong, Y.; Yi, T. (J. Mater. Chem. B, 2019)

(untitled) - Maity, D.; Li, M.; Ehlers, M.; Schmuck, C. (Chem. Commun., 2017)

(untitled) - Xu, Z.; Singh, N. J.; Lim, J.; Pan, J.; Kim, H. N.; Park, S.; Kim, K. S.; Yoon, J. (J. Am. Chem. Soc., 2009)

(untitled) - Li, X.; Guo, X.; Cao, L.; Xun, Z.; Wang, S.; Li, S.; Li, Y.; Yang, G. (Angew. Chem., Int. Ed., 2014)

(untitled) - Nishizawa, S.; Kato, Y.; Teramae, N. (J. Am. Chem. Soc., 1999)

(untitled) - Noguchi, T.; Shiraki, T.; Dawn, A.; Tsuchiya, Y.; Ngoc Lien, L. T.; Yamamoto, T.; Shinkai, S. (Chem. Commun., 2012)

(untitled) - Huang, L.-X.; Guo, Q.; Chen, Y.; Verwilst, P.; Son, S.; Wu, J.-B.; Cao, Q.-Y.; Kim, J. S. (Chem. Commun., 2019)

(untitled) - Xu, H.-R.; Li, K.; Jiao, S.-Y.; Pan, S.-L.; Zeng, J.-R.; Yu, X.-Q. (Analyst, 2015)

(untitled) - Ma, H.; Yang, M.; Zhang, C.; Ma, Y.; Qin, Y.; Lei, Z.; Chang, L.; Lei, L.; Wang, T.; Yang, Y. (J. Mater. Chem. B, 2017)

(untitled) - Alcalde, E.; Mesquida, N.; Vilaseca, M.; Alvarez-rúa, C.; García-Granda, S. (Supramol. Chem., 2007)

(untitled) - Ahmed, N.; Shirinfar, B.; Geronimo, I.; Kim, K. S. (Org. Lett., 2011)

(untitled) - Wang, D.; Zhang, X.; He, C.; Duan, C. (Org. Biomol. Chem., 2010)

(untitled) - Kwon, J. Y.; Singh, N. J.; Kim, H. N.; Kim, S. K.; Kim, K. S.; Yoon, J. (J. Am. Chem. Soc., 2004)

(untitled) - Maity, D.; Assaf, K. I.; Sicking, W.; Hirschhäuser, C.; Nau, W. M.; Schmuck, C. (Chem. – Eur. J., 2019)

(untitled) - Winnik, F. M. (Chem. Rev., 1993)

(untitled) - Ge, Y.; Wen, Y.; Liu, H.; Lu, T.; Yu, Y.; Zhang, X.; Li, B.; Zhang, S.-T.; Li, W.; Yang, B. (J. Mater. Chem. C, 2020)

(untitled) - Biswas, R.; Naskar, S.; Ghosh, S.; Das, M.; Banerjee, S. (Chem. – Eur. J., 2020)

(untitled) - Kumari, N.; Dey, N.; Jha, S.; Bhattacharya, S. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Černochová, J.; Branná, P.; Rouchal, M.; Kulhánek, P.; Kuřitka, I.; Vícha, R. (Chem. – Eur. J., 2012)

(untitled) - Yang, C.; Mehmood, F.; Lam, T. L.; Chan, S. L.-F.; Wu, Y.; Yeung, C.-S.; Guan, X.; Li, K.; Chung, C. Y.-S.; Zhou, C.-Y.; Zou, T.; Che, C.-M. (Chem. Sci., 2016)

(untitled) - Haedler, A. T.; Misslitz, H.; Buehlmeyer, C.; Albuquerque, R. Q.; Köhler, A.; Schmidt, H.-W. (ChemPhysChem, 2013)

(untitled) - Kalyanasundaram, K.; Thomas, J. K. (J. Am. Chem. Soc., 1977)

(untitled) - Somerharju, P. (Chem. Phys. Lipids, 2002)

(untitled) - Karpovich, D. S.; Blanchard, G. J. (J. Phys. Chem., 1995)

(untitled) - Lehrer, S. S. (Subcell. Biochem., 1995)

Photophysics of aromatic Molecules - Birks, J. B. (Wiley-Interscience, 1970)

(untitled) - Chan, C. W.; Smith, D. K. (Chem. Commun., 2016)

(untitled) - Jiao, Q.; Liu, Q. (Anal. Lett., 1998)

(untitled) - Gribble, F. M.; Loussouarn, G.; Tucker, S. J.; Zhao, C.; Nichols, C. G.; Ashcroft, F. M. (J. Biol. Chem., 2000)